High value markers linked to major gene for MLN tolerance in maize. - CGIAR Research Program on Maize (2018)
High value, high quality markers have been deployed for use for breeding for MLN tolerance in maize. The markers have been made available for use through the HTPG project of EiB and have been successfully used by the CIMMYT GMP team in east Africa.